SURFACE PLASMON RESONANCE (SPR) ON METALLIC FILM COATED GRATING STRUCTURE FOR SURFACE- ENHANCED RAMAN SPECTROSCOPY (SERS) SUBSTRATE AS PESTICIDE DETECTOR - Hafizhatul Ulum, Afrida
A pesticide sensor detector has been developed based on Surface-Enhanced Raman Spectroscopy (SERS). One of the methods to enhance Raman signal is Surface Plasmon Resonance (SPR). SPR is a resonance phenomenon between plasmon (electrons on metallic surface) with electromagnetic wave. The simulation of SERS substrate geometry has been done using Rigorous-Coupled Wave Analysis (RCWA) method that is run in Matlab software. The fabricated grating structure has a periodicity of 850 nm and a grating depth of 310 nm. Gold metal coating on the grating structure is done by varying the deposition time of 5 s, 10 s, 15 s, 30 s, 45 s, 90 s and 180 s. The structure is fully characterized by a Scanning Electron Microscope (SEM) and Raman. We tested Methylene Blue (MB) and Methyl Parathion (MP) as target solutions on the substrate. The gold deposition time that showed the peak of the Raman from the analytes occurred at 45 s, 90 s and 180 s in MB measurements with concentrations of 10?3and 10?4M. The highest intensity was achieved in structures with gold deposition time 180 s. In this structure, the operating pressure in the sputtering technique varied with 3 mTorr, 5 mTorr and 10 mTorr. The structure tested on with MB concentration 10?3and 10?4M and with MP concentration 10?2M. The highest intensity was obtained on the substrate with an operating pressure of 3 mTorr.